A single-centre cohort of patients with systemic light chain AL-amyloidosis treated with conventional chemotherapy or with high-dose chemotherapy and autologous stem cell transplantation (Swiss Medical Weekly, 2014)
BACKGROUND: High-dose chemotherapy (HDCT) with autologous stem cell transplantation (ASCT) has been reported to confer better prognosis in systemic light chain AL-amyloidosis as compared with conventional chemotherapy. However, only limited data are available so far on treatment and outcome of AL-amyloidosis patients in Switzerland. METHODS: Within a single-centre cohort of patients with biopsy confirmed AL-amyloidosis diagnosed between January 1995 and December 2012, we aimed to investigate treatment effects in patients treated with conventional chemotherapy versus HDCT with ASCT. RESULTS: We identified 50 patients with AL-amyloidosis treated with conventional chemotherapy and 13 patients who received HDCT with ASCT. Clinical characteristics differed between the groups for the age of the patients (59 years for patients with ASCT/HDCT vs 69 years; p= 0.0006) and the troponin-T value (0.015 μg/l vs 0.08 μg/l; p = 0.0279). Patients with ASCT showed a trend towards better overall survival, with median survival not yet reached compared with 53 months in patients on conventional chemotherapy (p = 0.0651). CONCLUSION: Our results suggest that light chain AL-amyloidosis patients considered fit to undergo HDCT and ASCT may have a better outcome than patients treated exclusively with conventional chemotherapy regimens; however, the better performance status of patients receiving HDCT may have added to this treatment effect.